HIV/AIDS Risk among the Children of Bangladesh - Zahan, Nasrin (ABC Journal of Advanced Research, 2013)
Everyday more than thousands of people are becoming infected with HIV/AIDs worldwide nearly half of them are women. According to the joint United Nations Program on HIV/AIDs (JNAIDs) “2010 Report on the Global Aids Epidemic”, 2.5 million children around the world are living with HIV/AIDs. Most HIV infections are passed from mother to child during pregnancy. Bangladesh as a developing country, in spite of resource scarcity, has been operating some significant policy initiatives with the active role from both governmental and non-governmental bodies to prevent and mitigate the impact of the epidemic in the families. Though there is, no notable program running in Bangladesh especially for children developed awareness as well as preventing them from HIV and AIDS. This Study reviews current knowledge of mother-to-child HIV transmission in developing countries, summarizes key findings from the trials, outlines future research requirements, and implementing prenatal HIV prevention interventions in resource-poor settings. Successful implementation of available prenatal HIV interventions could substantially improve global child survival. As for this, to formulate a complete strategy and action plan in both national and local level for this alarming issue is an utmost necessity.